Interactive Storytelling Using Profession Pictures and Storybooks for Children’s Language Acquisition (PIAUD IAIN Kudus, 2024)
This study investigates the impact of profession pictures and storybooks on children’s language acquisition. Employing a qualitative descriptive approach, data were collected through direct observation, structured interviews, and documentation. The study involved children aged 5–6 years at Piri Nitikan Kindergarten, Yogyakarta. The storytelling sessions were divided into two groups: one utilizing profession pictures and the other using storybooks. The findings revealed that profession pictures stimulated children’s curiosity and fostered active participation, resulting in notable vocabulary expansion and the use of more complete sentences. Conversely, storybooks enhanced children’s comprehension of narrative structures and encouraged using descriptive language. Both methods promoted meaningful engagement and dynamic learning experiences, offering valuable insights for educators. This study underscores the complementary advantages of profession pictures and storybooks in addressing diverse learner needs, fostering an engaging and effective language acquisition environment.